Wind Flow Analysis on Software-Based U-Type Savonius Wind Turbine Blades Using Solidworks Flow Simulation - Muhammad Aulia; Randi Purnama Putra; Andre Kurniawan; Fitrah Qalbina (Jurnal Vokasi Mekanika (VoMek), 2026)
Savonius wind turbines are a type of vertical axis wind turbines that work based on the principle of drag force. The way this turbine works begins with a gust of wind that hits the turbine blades which are generally semi-cylindrical or resemble the letter "U". When the wind blows, the side of the blade facing directly in the direction of the wind will receive a greater thrust, while the side of the blade facing the wind will receive a smaller thrust, resulting in a difference in force that causes the turbine to rotate. This study aims to analyze the performance of savonius wind turbines based on the value of power coefficient (Cp) and torque coefficient (Ct) at wind speed variations. The method used in this study is a numerical method with a Computational Fluid Dynamics (CFD) approach. Simulations were carried out at wind speed variations of 3 m/s, 5 m/s, and 7 m/s to determine the effect of changes in wind speed on the flow characteristics and performance of the turbine. The simulation results showed that the value of the power coefficient (Cp) and the torque coefficient (Ct) were in the range of 0.140 to 0.157. This value changes as the wind speed increases, which shows that the variation in wind speed affects the performance of the savonius wind turbine. Based on these results, it can be concluded that the Savonius wind turbine has good potential to be used in areas with low to medium wind speeds.